Optimized Design of a Sonar Transmitter for the High-Power Control of Multichannel Acoustic Transducers - Lee, Byung-Hwa; Baek, Ji-Eun; Kim, Dong-Wook; Lee, Jeong-Min; Sim, Jae-Yoon (Electronics (Basel), 2021)
For driving multichannel underwater acoustic transducers, the integrated design of the transmitter based on the analysis of the widely distributed impedance should be considered. Previous studies focused on either the matching circuit or the fast resonant tracking control. This paper proposes the design and control methods of a sonar transmitter based on the analysis of the impedance distribution. For the transmitter design, the optimization method based on the particle swarm optimization (PSO) algorithm is proposed for estimating the equivalent and matching circuit parameters. The equivalent circuits of the transducer are more precisely designed by using the measured data in both air and water. The fitness function proposed in the matching includes special functions, such as the limitation and parasitic inductances. A comparison of the experimental and simulation results shows that the optimized matching design improved the power factor, and was similar to the experimental result. For the transmitter control, the constant power and voltage control (CPVC) and instant voltage and current control (IVCC) methods are proposed for the variable impedance load. The impedance variation range affects the rated power and rated voltage of the transmitter, and the rating range determines the initial modulation index (MI) of the pulse-width modulation (PWM) control. To verify the control method, an experimental setup including the multichannel acoustic transducers was established. As a result, the constant power and constant voltage were verified with the proposed control, and the instant voltage and current control also worked in the event that the instant voltage or current exceed their threshold values.